2022
DOI: 10.1186/s13148-022-01248-0
|View full text |Cite
|
Sign up to set email alerts
|

Atheroprotective mechanism by which folic acid regulates monocyte subsets and function through DNA methylation

Abstract: Background Recent studies have suggested that folic acid can restore abnormal DNA methylation and monocyte subset shifts caused by hyperhomocysteinemia (HHcy) and hyperlipidemia (HL). However, the exact mechanism of action is still not fully understood. In this study, we further investigated the reversal effect and underlying mechanism of folic acid on the shift in monocyte subsets induced by aberrant lipids and Hcy metabolism via DNA methylation in vitro and in vivo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In the first reaction, Hcy is catalyzed by methylcobalamin-containing methionine synthase (MS) to form methionine and tetrahydrofolate (THF) via receiving methyl from 5-methylTHF ( 16 ). Thus, Hcy metabolism generates cross-link with intracellular folate metabolism ( 17 ), which is also an important reason for folate level affect Hcy metabolism. In the second reaction, betaine-dependent remethylation backs Hcy to methionine by betaine-homocysteine methyltransferase (BHMT) ( 18 ).…”
Section: Homocysteine Metabolismmentioning
confidence: 99%
“…In the first reaction, Hcy is catalyzed by methylcobalamin-containing methionine synthase (MS) to form methionine and tetrahydrofolate (THF) via receiving methyl from 5-methylTHF ( 16 ). Thus, Hcy metabolism generates cross-link with intracellular folate metabolism ( 17 ), which is also an important reason for folate level affect Hcy metabolism. In the second reaction, betaine-dependent remethylation backs Hcy to methionine by betaine-homocysteine methyltransferase (BHMT) ( 18 ).…”
Section: Homocysteine Metabolismmentioning
confidence: 99%
“…In the short term, folate can bind to lead ions to form insoluble complexes, promoting the excretion and detoxi cation of lead [29]. Over the long term, folate affects DNA methylation, in uencing the expression of genes related to monocyte function and lead toxicity [30]. Animal studies suggest that folate not only affects lead metabolism but also protects against lead-induced oxidative damage [31].…”
Section: Discussionmentioning
confidence: 99%
“…Our teams have also shown that, through modulating the maturation of miR-210 that targets AIFM3 mRNAs, it regulates cardiomyocyte health and the progression of cardiac dysfunction, implicating the differential regulations of miRNA biogenesis in cardiomyocytes under hypoxia [ 29 ]. Epigenetic regulations, not only including miRNAs, DNA methylation, and histone modification, have also been implicated in the myocardial protection process [ 41 , 42 ]. Recently, m 6 A methylation of RNA has also come into prominence as a new important mechanism regulating various biological processes [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%